2014
DOI: 10.1111/jog.12307
|View full text |Cite
|
Sign up to set email alerts
|

Determining optimal gestational weight gain in a multiethnic Asian population

Abstract: The results of this study, the first to determine optimal GWG in the multiethnic Singaporean population, concur with the Institute of Medicine (IOM) guidelines in that GWG among Asian women who are heavier prior to pregnancy, especially those who are obese, should be lower. However, the optimal GWG for underweight and obese women was outside the IOM recommended range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 26 publications
3
43
0
Order By: Relevance
“…The management of GWG using official guidelines has been implemented globally [1,2,13,[20][21][22][23]. According to a prospective cohort study in the USA, GWG within the levels recommended by the Institute of Medicine (IOM) guidelines was associated with a decreased risk of delivering LBW babies [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of GWG using official guidelines has been implemented globally [1,2,13,[20][21][22][23]. According to a prospective cohort study in the USA, GWG within the levels recommended by the Institute of Medicine (IOM) guidelines was associated with a decreased risk of delivering LBW babies [1].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women must continuously monitor their body weight during pregnancy using their country's official criteria. The differences in the recommended GWG values between Japan and other countries could be due to differences in body composition between races [2,11,19,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal weight gain is much more with high BMI. Like in the study by Ee et al (7) in 2014 showed antenatal weight gain among Asian women who are obese, should be lower. However, the optimal weight gain for underweight and obese women was outside the IOM recommended range.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown at this time whether more stringent criteria for overweight and obesity among Asian populations to prevent chronic disease (WHO Expert Consultation, 2004) might also be appropriate for GWG, or what the impact of using these might be on birth weight and perinatal outcomes. Exploring this issue in existing large datasets, as in the study by Ee et al (2014), would contribute to better understanding of weight-related issues for Asian women throughout their lifespans.…”
Section: Implications For Policy And/or Practicementioning
confidence: 97%